Теоретична модель ринку праці молодих інженерів на основі теорії соціального поля П. Бурдьє - Садовська, Альона Олегівна (НТУ "ХПІ", 2017)
Запропоновано підхід, заснований на теорії сучасного французького соціолога П. Бурдьє. Ринок праці в цілому і ринок праці молодих інженерів, зокрема, розглядається як специфічне соціальне поле або соціальний підпростір, де відбуваються певні взаємодії, транзакції, рух трудових ресурсів і фінансового капіталу. Використовуються, традиційні для підходу П. Бурдьє, поняття «агенти поля», «практики», «конфлікт», «боротьба за капітал» тощо. Таким чином, ринок праці відповідно до методології Бурдьє постає не тільки як мережа економічних або соціальних відносин, а, передусім, як певного роду набір практик, властивих тим або іншим соціальним групам.

The proposed approach is based on the theory of modern French sociologist P. Bourdieu. The labor market in general and the labor market of young engineers, in particular, are considered as a specific social field or social subspace, where certain interactions, transactions, movement of labor and financial capital occur. Used, traditional for the approach of P. Bourdieu, the concept of "agents of the field", "practice", "conflict", "struggle for capital" etc. Thus, the labor market in accordance with the methodology of Bourdieu appears not only as a network of economic or social relations, but, above all, as a kind of set of practices that are specific to one or another social group. It should be noted that this approach is not completely new. In conceptual terms, it was observed already in the early twentieth century in the works of P. Sorokin and G. Simmel. The German sociologist considered the society not only as a subjective entity (form I), but also as a certain objective scheme. In the second sense, society turns into a stable, structured space, which absorbs all positions. His simplistic model can be a bureaucracy that dissipated in their posts, like a sparrow on a tree, with each branch - "position".
Theoretical model of the labor market of young engineers based on the theory of social field P. Bourdieu
Keywords: габітус; суспільство; придатність професійна; habitus; young engineers; labor market; society; theory of social field